Answer to dengue and chikungunya: specific antiviral therapy - Ghosh, Mrinmay (International Journal of Advances in Medicine, 2017)
Dengue is probably the most important arthropod borne viral disease worldwide, with 50-100 million infections occurring per year. Year-round transmission of dengue viruses of serotype 1-4 is prevalent globally. Vectors are Aedes aegypti and Aedes albopictus. Laboratory diagnosis by ELISA for IgM or RT-PCR, Incubation period 4-7days, sudden onset of fever, frontal headache, retro orbital pain, back pain with severe myalgia, a transient macular rash on the first day, lymphadenopathy, palatal vesicles, scleral infections. Illness may last a week with clinical signs; anorexia, nausea, vomiting, marked cutaneous maculopapular rash on trunks spreading to extremities and face on defervescences on days 3-5. Epistaxis, scattered petechiae and preexisting gastrointestinal lesions may bleed during acute phase.